EFFICIENCY OF PNEUMOCOCCAL VACCINE IN CHILDREN WITH DIFFERENT PATTERNS OF TUBERCULOSIS INFECTION - I. F. Dovgalyuk (SPb RAACI, 2017)
Concomitant infection is known to decrease non-specific immunity levels, thus negatively affecting clinical outcomes in tuberculosis patients. Development of specific immune response against most common pediatric infections, e.g., pneumococcal infection, is possible both in children with latent tuberculosis and in respiratory tuberculosis. The study contains data concerning results of immunization with Pneumo23 vaccine against pneumococcal infection in 35 children (3 to 14 years old) with different manifestations of MBT infection observed at the St. Petersburg Research Institute of Phthisiopulmonology. The vaccination efficiency was evaluated by incidence of acute respiratory infectionsm acute otitis media, and community pneumonias within one year before and after vaccination performed. Clinical safety of the vaccination was determined as the number of general and local reactions registered following vaccination.Incidence of post-vaccinal reactions did not differ significantly between the clinical groups and did not exceed the values reported by the vaccine manufacturer. Post-vaccinal period was event-free in 94.3% of vaccinated children, without any negative effects upon the underlying tuberculosis process. In Group 2, all the children were complication-free over the post-vaccinal period. Both groups exhibited a statistically significant increase of IGg levels by the post-vaccination day 14…45. The PPV23 vaccination was not followed by postvaccinal complications, or worsening of tuberculosis infection. Hence, anti-pneumococcal vaccination is effective for prevention of acute respiratory infections, both in MBT-infected children and in patients with local tuberculosis affection.